Public Finance - Rosen, Harvey S (McGraw-Hill Education, 2014)
Provides the economic tools necessary to analyze government expenditure and tax policies and, along the way, takes students to the frontiers of current research and policy. While the information presented is cutting edge and reflects the work of economists currently active in the field, the approach makes the text accessible to undergraduates whose only prior exposure to economics is at the introductory level.